The impact of the temperature and exploitation time on the tensile properties and plain strain fracture toughness, KIc in characteristic areas of welded joint - Simon Sedmak; Ivica Čamagić; Aleksandar Sedmak; Zijah Burzić; Mihajlo Aranđelović (Fracture and Structural Integrity, 2018)
This paper presents the analysis of the temperature and exploitation time impact on the resistant measure to brittle fracture of welded joint constituents of the new and exploited low-alloyed Cr-Mo steel A-387 Gr. B from the aspect of application of the parameters obtained by tensile testing and parameters obtained by fracture mechanics testing. The exploited parent metal is a part of the reactor mantle which has been exploited for over 40 years and is in the damage repair stage, i.e. in the stage where the part of the mantle is being replaced with new material. Basic characteristics of the material strength, as well as the stress-elongation curves required for stress analysis are obtained by tensile testing. The testing of plane strain fracture toughness is conducted in order to determine the critical stress intensity factor, KIc, that is, assessment of behavior of the new and exploited parent metal, welded metal and heat affected zone from the side of the new parent metal and from the side of the exploited parent metal in the presence of the crack type error. Based on the research results, the analysis of the resistance to brittle fracture represents the comparison of obtained values for characteristic areas of welded joint and justification of the selected welding technology.